The Correlation Between English Language Learning Strategies And Students Thinking Style At The Second Grade Of Man 1 Kolaka - Ray Suryadi; Firdayana Kamaruddin (English Education Department at FKIP Nommensen University, 2022)
This research was conducted at MAN 1 Kolaka. The objective of this reaseach is to find out information and data weather there is any correlation between English language learning strategy and students’ thinking style at the second grade AGAMA I of MAN 1 Kolaka. The research design is descriptive quantitative. The data were collected through questionnaires. English Language Learning Strategy at the second grade AGAMA I of MAN 1 Kolaka are Metacognitive with the total frequency is 47% percent and Studets’ Thinking Style are Extrovert with the total persentage is 53%. The Population of the research was the second grade students of MAN 1 Kolaka and the sample of the research was class AGAMA I which consisted of 15 students. The data analysis used in this research was product moment formula which showed that there was no any correlation between English Language Learning Strategy and Students’ Thinking Style. It could be synthesized that hypothesis were r-count was lower than r-table. So H1 was rejected and H2 was accepted. The coefficient Correlation between English Language Learning Strategies and Students’ Thinking Style did not have any significant correlation with the r-count = -0,218 was lower than r-table 0,514 at the significance level 5% and degree of freedom (df) was 15 (-0,218>0,514). Therefore, it was categorized as low correlation. H0 and H1 was rejected and H2 was accepted.